2012
DOI: 10.1242/jcs.109421
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of polarized lysosome exocytosis in epithelial cells

Abstract: There was an error published in J. Cell Sci. 125, 5937-5943.In Fig. 4B the same image was inadvertently presented as the xy section (top panels) of syntaxin 4 staining in MDCK wild-type and MDCK m1A-KD cells. In the correct version (shown below), the appropriate xy image for m1A-KD (top panel, middle) matches the corresponding xz panel (bottom panel) that was part of the original figure.The mistake in the figure did not affect the conclusions of the paper. Fig. 4B is shown below. The correctThe authors apologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 49 publications
2
54
0
Order By: Relevance
“…Lysosome exocytosis causes transient appearance of lysosomal membrane proteins (e.g., LAMP2) on the plasma membrane and release of lysosomal hydrolases such as β-hexosaminidase (β-hex) into the extracellular medium (25). We detected LAMP2 on the RPE cell surface after a 10-min exposure to either 10% NHS (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Lysosome exocytosis causes transient appearance of lysosomal membrane proteins (e.g., LAMP2) on the plasma membrane and release of lysosomal hydrolases such as β-hexosaminidase (β-hex) into the extracellular medium (25). We detected LAMP2 on the RPE cell surface after a 10-min exposure to either 10% NHS (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…We have shown that excess cholesterol in RPE with vitamin A dimers activates ASMase, which interferes with organelle traffic by acetylating microtubules (MT) (20). To investigate how excess cholesterol and MT acetylation impacts CD59 trafficking, we treated RPE monolayers with either U18666A to increase cholesterol (25) and, thereby, acetylated MT (20), or with the HDAC6 inhibitor tubacin, which prevents MT deacetylation (26). Similar to A2E, both drugs decreased cell surface CD59 and increased MAC deposition after complement exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In polarized epithelial cells, lysosomal exocytosis is directed toward the basolateral membranes, but not the apical membranes ( 74 ). The directionality of lysosomal exocytosis in these cells could be caused by the localization of the plasma membrane SNARE, syntaxin4, exclusively at the basolateral membrane, resulting in a "polarized" formation of the SNARE complex ( 74 ).…”
Section: Directionality Of Lysosomal Exocytosismentioning
confidence: 99%